Minoxidil versus placebo in the treatment of arterial wall hypertrophy in children with Williams Beuren Syndrome: a randomized controlled trial - Behrouz Kassai; Philippe Bouyé; Brigitte Gilbert-Dussardier; François Godart; Jean-Benoit Thambo; Massimiliano Rossi; Pierre Cochat; Pierre Chirossel; Stephane Luong; André Serusclat; Isabelle Canterino; Catherine Mercier; et al. (BMC, 2019)
Abstract Background Insufficient elastin synthesis leads to vascular complications and arterial hypertension in children with Williams-Beuren syndrome. Restoring sufficient quantity of elastin should then result in prevention or inhibition of vascular malformations and improvement in arterial blood pressure. Methods The aim of this study was to assess the efficacy and safety of minoxidil on Intima Media Thickness (IMT) on the right common carotid artery after twelve-month treatment in patient with Williams-Beuren syndrome. We performed a randomized placebo controlled double blind trial. All participants were treated for 12 months and followed for 18 months. The principal outcome was assessed by an independent adjudication committee blinded to the allocated treatment groups. Results The principal outcome was available for 9 patients in the placebo group and 8 patients in the minoxidil group. After 12-month treatment, the IMT in the minoxidil group increased by 0.03 mm (95% CI -0.002, 0.06) compared with 0.01 mm (95%CI - 0.02, 0.04 mm) in the placebo group (p = 0.4). Two serious adverse events unrelated to the treatment occurred, one in the minoxidil and 1 in the placebo group. After 18 months, the IMT increased by 0.07 mm (95% CI 0.04, 0.10 mm) in the minoxidil compared with 0.01 mm (95% CI -0.02, 0.04 mm) in the placebo group (p = 0.008). Conclusion Our results suggest a slight increase after 12 and 18-month follow-up in IMT. More understanding of the biological changes induced by minoxidil should better explain its potential role on elastogenesis in Williams-Beuren syndrome. Trials registration US National Institutes of Health Clinical Trial Register (NCT00876200). Registered 3 April 2009 (retrospectively registered).